Regulation of the placental BCRP transporter by PPAR gamma. Issue 5 (23rd November 2016) - Lin, Yixin; Bircsak, Kristin M.; Gorczyca, Ludwik; Wen, Xia; Aleksunes, Lauren M.
Abstract: Identifying regulators of placental breast cancer resistance protein (BCRP) expression is critical as downregulation of this transporter may increase exposure of the fetus to xenobiotics. Here, we sought to test whether the nuclear receptor peroxisome proliferator‐activated receptor γ (PPARγ) regulates BCRP expression in the placenta. To test this, human BeWo placental choriocarcinoma cells were cultured with the PPARγ agonist rosiglitazone or the PPARγ antagonist T0070907 for 24 h. Messenger RNA (mRNA) expression of syncytialization markers, GCM1 and hCGβ, as well as BCRP increased with PPARγ agonist treatment. Conversely, BCRP mRNA and protein expression decreased 30%–50% with PPARγ antagonist treatment. Rosiglitazone enhanced BCRP protein expression and transport activity, resulting in a 20% greater efflux of the substrate Hoechst 33342 compared with control cells. These results suggest that PPARγ can upregulate BCRP expression in the placenta, which may be important in understanding mechanisms that protect the fetus from xenobiotic exposure during development.